Functional Gastrointestinal Disorders in Infants: Long-Tern Consequences and Modern Approaches for Prevention and Treatment - Evgeniya G. Makarova; Sergei E. Ukraintsev (Union of pediatricians of Russia, 2017)
The article discusses modern ideas about the genesis of the most common variants of functional gastrointestinal disorders (FGID) in infants, and their ability to lead to long-term negative consequences for the health of the child. The article provides data on role of intestinal microbiota in development of FGID in infants and current approaches to prevention and correction using probiotics with proven effectiveness.